Systematic Literature Review: Trends Literacy Numeration in Maritime Materials Teaching Materials in the Digital Era - Nuryati, Nuryati; Hufad, Achmad; Rusdiyani, Isti (PT. Riset Press International, 2024)
Study This aim for do a Related literature review on trend literacy teaching materials numeration in the material maritime For child age early in the digital era. Research methods used _ in the study This is the SLR (Systematic Literature Review) method. Data collection was carried out with document articles that have been studied similarly. The articles used are 17 articles from some journals national and international indexed by Google Scholar Semantic Scholar and Scopus published in 2013-2023, based on a study found that teaching materials _ maritime form printed and digital teaching materials. Printed maritime teaching materials in the form of modules, comic media, learning models Webb, form songs, form book education characters, suitcase media literacy, and form products. Whereas teaching materials in digital form only One teaching material viz shaped book story digital illustration entitled Baso and Pinisi For increase culture maritime child. Therefore _ that's necessary done develop teaching materials _ maritime so that it can help children increase their literacy and numeracy related to culture maritime in children's age early in a way maximum. Study This expectation can give insight and knowledge for teachers and parents specifically material, so can increase inner teacher creativity in making teaching materials. Study This clarifies and explains research previously about trend teaching materials _ maritime For growing literacy numeracy child age early in the digital era. And based on searches carried out Not yet found a study with the same topic.